2017
DOI: 10.1002/2016ja023708
|View full text |Cite
|
Sign up to set email alerts
|

Identifying intervals of temporally invariant field‐aligned currents from Swarm: Assessing the validity of single‐spacecraft methods

Abstract: Field‐aligned currents (FACs) are a fundamental component of coupled solar wind‐magnetosphere‐ionosphere. By assuming that FACs can be approximated by stationary infinite current sheets that do not change on the spacecraft crossing time, single‐spacecraft magnetic field measurements can be used to estimate the currents flowing in space. By combining data from multiple spacecraft on similar orbits, these stationarity assumptions can be tested. In this technical report, we present a new technique that combines c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 19 publications
5
46
0
1
Order By: Relevance
“…This aspect, in line with previous observations (see, e.g., Forsyth et al, 2017;, adversely influences the outcome of the dual-s/c estimation. In the latter, the fine structure of FAC density is revealed.…”
Section: Dual-s/c Methods On Configurations That Use Simultaneous Meassupporting
confidence: 90%
See 1 more Smart Citation
“…This aspect, in line with previous observations (see, e.g., Forsyth et al, 2017;, adversely influences the outcome of the dual-s/c estimation. In the latter, the fine structure of FAC density is revealed.…”
Section: Dual-s/c Methods On Configurations That Use Simultaneous Meassupporting
confidence: 90%
“…The latter condition is usually checked by performing a cross-correlation analysis (see, e.g., in Forsyth et al, 2017 a more involved technique has been used that combines cross correlation and linear fitting). The latter condition is usually checked by performing a cross-correlation analysis (see, e.g., in Forsyth et al, 2017 a more involved technique has been used that combines cross correlation and linear fitting).…”
Section: Applicability Of the Three-s/c Methodsmentioning
confidence: 99%
“…These authors explained such features as occurring as a natural result of R1 and R2 current closure in the auroral zone due to the fact that Pedersen current and its associated electric field reach a maximum at the R1-R2 boundary; they labelled these features Birkeland current boundary flows (BCBFs). Forsyth et al, 2017). The disturbances shown in Figures 11 and 12 are clearly electromagnetic and polarized in the transverse plane, similar to the other time periods considered in this paper.…”
Section: 1029/2019ja027277supporting
confidence: 75%
“…Similarly, such nonstationarity will pollute the two-spacecraft ESA Swarm FAC product as well. The Swarm A single-(blue line at 1-Hz resolution) and dual-spacecraft (red line, 20-s low-pass filtered, 1-Hz resolution; Ritter et al, 2013) FAC estimates in panel c imply significant small-scale electrodynamics, producing fine structure in the single-spacecraft FAC estimate but which most likely violate the quasi-static approximation (e.g., Forsyth et al, 2017). The importance of small-scale electrodynamics is further analysed and emphasized in Figure 4, which demonstrates the impact of applying a 20-s filter as compared to studies using 16-sps data.…”
Section: Consistent With the Global Ampere Fac Map Shown Inmentioning
confidence: 99%
“…Here, we incorporate additional analysis steps consisting of the application of the CHAOS-6 model (prior to the wavelet analysis) and the utilization of Swarm Level 2 products (i.e., the FAC and IBI products) to impose constraints on the Swarm data for the wave event selection. Forsyth et al (2017) suggested that many of the magnetic field perturbations on small scales may contain a significant fraction of perturbations which are the result of wave activity in the vicinity of the spacecraft or current sheets inclined to the motion of the spacecraft. As a result, they noted that extreme care must be taken in interpreting the temporal variation of the magnetic field observed by a moving spacecraft as relating to the spatial structures which can be used to infer field-aligned currents.…”
Section: Data Processing and Analysis Techniquementioning
confidence: 99%